WAIS Divide WDC06A Oxygen Isotope Record - Steig, Eric J. (IEDA: US Antarctic Program Data Center, 2015)
This data set contains complete low resolution (0.25 to 100 cm) oxygen isotope data from the WAIS Divide Ice Core WDC06A, 0 to 3404.7 m depth. Also included is the WDC2014 timescale.